Effects of oil film thickness and viscosity on the performance of misaligned journal bearings with couple stress lubricants. (June 2020) - Zheng, Liangyan; Zhu, Hanhua; Zhu, Junchao; Deng, Yibin
Abstract: This paper investigated the performance characteristics of misaligned journal bearing lubricated using couple stress fluids. Based on micro-continuum theory, the modified Reynolds equation for couple stress lubricants was developed, in which viscosity-pressure effect was considered. By setting the critical oil film thickness, the region with couple stress effect can be recognized. The ratio of the critical oil film thickness to couple stress parameter was referred to as film thickness coefficient. It was found from results that increase of film thickness coefficient can significantly improve the maximum film pressure and high-pressure area, when film thickness coefficient was smaller than 4. Viscosity-pressure effect was capable of enhancing viscosity, friction coefficient and the maximum film pressure, and reducing couple stress parameter, especially for large misalignment angle. Highlights: The critical oil film thickness was proposed to discriminate couple stress fluid from Newtonian fluid. The film thickness coefficient signified an improvement in the maximum film pressure and high-pressure area. Viscosity-pressure effect was applied to develop a modified Reynolds equation for couple stress fluids. Viscosity-pressure effect provided a reduction in couple stress parameter, especially at high values of misalignment angle.